Role of duckweed (Lemna minor L.) harvesting in biological phosphate removal from secondary treatment effluents - Öbek, E; Hasar, H (Parlar Research & Technology Ug, 2002)
The conventional wastewater treatment plants can partly remove phosphorus. When the effluents of secondary treatment are discharged to particularly inland water bodies, they cause eutrophication in the receiving environment. Phosphate is a limiting factor and must be removed from the effluent before being discharged. The capacity of duckweed (Lemna minor L.) in phosphate removal from secondary effluents was studied in laboratory to understand the mechanism of biological phosphate uptake. Orthophosphate can be efficiently removed if duckweed is frequently harvested. The initial phosphate concentration decreased from 15 mg L-1 to 0.5 mg L-1 at the end of an 8 days period.
Keywords: biological phosphate uptake; duckweed; harvesting